SELF-REPORTED HEALTH, ILLNESS AND SELF-CARE AMONG DOCTORS OF MEERUT - Bansal, Rahul; Katyal, Rashmi; Haji, Sartaj Ahmed; Kumari, Ranjeeta (Indian Journal of Community Health, 2012)
Abstract: This document provides insight on lifestyle and healthcare status of doctors based on key findings from a survey conducted in Meerut City, (U.P.) India. Objectives: 1.To study the lifestyle pattern among the doctors of Allopathy and Ayurveda & teachers of local private Medical college, local private Dental college. 2. To study the (self-reported) prevalence of common non-communicable diseases in the same. 3. To know the pattern of healthy lifestyle practices adopted by the doctors. Material & Methods: The Cross-sectional study was conducted with the help of a pre-designed and pre-tested questionnaire which was filled by the faculty of local private Medical College, Dental college, Ayurvedic doctors and local practicing doctors of allopathy and Ayurveda. Verbal consent was implied. A purposive sample of 240 doctors [60 each from Medical and Dental colleges and 60 each from allopathy private practitioners (p.p.allo.) and ayurvedic private practitioners (p.p.ayur.)] were given the questionnaire-and response rate was 84%. The data was entered in Microsoft excel 2007 to know the frequency of the various lifestyle pattern. Results: 47.5% of the doctors had raised B.M.I. (Body Mass Index- more than 25); 21% of the doctors were smokers, 10% were current drinkers and 32% were hypertensive. Only 2.5% were found to be diabetic in our study. About 52% of the doctors exercised regularly. 32.5% were trained for yoga. Conclusion:This study implies that a large proportion of doctors themselves do not follow the healthy lifestyle and are having lifestyle diseases like obesity, hypertension etc. Interestingly, there was not much difference between doctors doing private practice or teaching in Medical/Dental College.